2017
DOI: 10.12659/ajcr.903886
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol as an Antiproteinuric Agent Can Result in the Deterioration of Renal and Heart Function in a Patient with Fabry Disease

Abstract: Patient: Female, 44Final Diagnosis: Deterioration of renal and heart functionSymptoms: HypercalcemiaMedication: —Clinical Procedure: LaboratorySpecialty: NephrologyObjective:Rare diseaseBackground:Fabry disease is a rare and progressive X-linked inherited disorder of glycosphingolipid metabolism that is due to deficient or absent lysosomal α-galactosidase A activity. Among its other associated signs and symptoms, patients present with renal failure and proteinuria, which are markers of disease progression. Ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Pisani et al showed that add-on 1-mg paricalcitol treatment reduced proteinuria from 2.1 g/14 h to 0.4 g/day over a 6-month period in patients with Fabry nephropathy who used an ACEi and/or ARB at the maximum tolerated dosage [ 53 ]. Although the ability of paricalcitol to control proteinuria is known, transient worsening of cardiac and renal functions associated with the use of paricalcitol has been described [ 54 ]. Trimarchi et al [ 55 ] proposed the potassium-sparing diuretic amiloride as a candidate adjuvant antiproteinuric agent in Fabry disease.…”
Section: Adjunctive Therapy For Fabry Nephropathymentioning
confidence: 99%
“…Pisani et al showed that add-on 1-mg paricalcitol treatment reduced proteinuria from 2.1 g/14 h to 0.4 g/day over a 6-month period in patients with Fabry nephropathy who used an ACEi and/or ARB at the maximum tolerated dosage [ 53 ]. Although the ability of paricalcitol to control proteinuria is known, transient worsening of cardiac and renal functions associated with the use of paricalcitol has been described [ 54 ]. Trimarchi et al [ 55 ] proposed the potassium-sparing diuretic amiloride as a candidate adjuvant antiproteinuric agent in Fabry disease.…”
Section: Adjunctive Therapy For Fabry Nephropathymentioning
confidence: 99%